Socialism, Identity and the Well-Being of Unemployed Women - Tom Günther; Jakob Conradi; Clemens Hetschko (CESifo GmbH, 2024)
Unemployment influences people's life satisfaction beyond negative income shocks. A large body of literature investigates these non-pecuniary costs of unemployment and stresses the importance of social identity and therefore social norms, especially for men. We add to this literature by showing that norm non-compliance may equally inflate the non-pecuniary loss of well-being for unemployed women. Drawing upon large-scale German panel data, we use the German division as a natural experiment to compare unemployment-related life satisfaction losses between different cohorts of East and West German women. We hypothesise that being exposed to different legal norms concerning workforce participation and different opportunity cost of working after the division shaped social identities and thus social norms around work for the two German female populations in different ways. Specifically, East German women were required to work full-time whereas West German women were expected to focus on family care. We find that East German women suffer significantly more from unemployment than West German women. This difference is driven by a significantly worse unemployment experience for East German females that were exclusively raised in the former GDR. We do not find such diverging patterns for German men. Our findings imply that women may suffer as much from unemployment as men, if socialised in the same way.
Keywords: P30; I31; J16; J60; N34; 330; well-being; gender; unemployment; social identity; social norms; German division